EVIDÊNCIAS CIENTÍFICAS SOBRE JUSTICIA NODICAULIS: UMA REVISÃO DE LITERATURA (CIPEEX, 2026)
Pain is a multifactorial phenomenon of clinical relevance, modulated by nociceptive and inflammatory processes. The search for therapeutic alternatives based on natural products has intensified, especially regarding plants from the Brazilian Cerrado biome, recognized for its plant diversity and richness in secondary metabolites. Objective: Among the species of the Acanthaceae family, several present compounds with analgesic, anti-inflammatory, and antioxidant properties, justifying interest in systematic research. Materials and Methods: This exploratory study conducted an integrative literature review in the PubMed, Web of Science, and Virtual Health Library databases, covering publications without temporal restrictions. Articles addressing botanical, phytochemical, and pharmacological aspects of the selected species were included, with emphasis on those still little studied in an experimental context. The screening of records occurred in stages, involving initial identification, title and abstract analysis, and full-text reading for eligibility. Conclusion: It is concluded that valuing Brazilian flora, combined with pharmacological prospecting methodologies, can support the discovery of new therapeutic candidates from plant resources.